Characterization of methicillin-resistant Staphylococcus aureus strains in sewage treatment plants in Tehran, Iran - Fateh Rahimi (IWA Publishing, 2021)
Multidrug-resistant Staphylococcus aureus strains have been commonly found in hospitals and communities causing wide ranges of infections among humans and animals. Typing of these strains is a key factor to reveal their clonal dissemination in different regions. We investigated the prevalence and dissemination of different clonal groups of S. aureus with resistance phenotype to multiple antibiotics in two sewage treatment plants (STPs) in Tehran, Iran over four sampling occasions. A total of 576 S. aureus were isolated from the inlet, sludge and outlet. Of these, 80 were identified as methicillin-resistant S. aureus (MRSA) and were further characterized using a combination of Phene Plate (PhP) typing, staphylococcal cassette chromosome mec (SCCmec), ccr types, prophage and antibiotic-resistant profiling. In all, eight common type (CT) and 13 single PhP type were identified in both STPs, with one major CT accounting for 38.8% of the MRSA strains. These strains belonged to three prophage patterns and five prophage types with SCCmec type III being the predominant type. Resistance to 11 out of the 17 antibiotics tested was significantly (P < 0.0059) higher among the MRSA isolates than methicillin-sensitive S. aureus (MSSA) strains. The persistence of the strains in samples collected from the outlet of both STPs was 31.9% for MRSA and 23.1% for MSSA. These data indicated that while the sewage treatment process, in general, is still useful for removing most MRSA populations, some strains with SCCmec type III may have a better ability to survive the STP process. HIGHLIGHTS Survival of MRSA in STPs has a major impact on public health if they enter surface waters.; Here we show that certain clones of MRSA carrying SCCmec type III have a better ability to survive treatment stages of the STPs.; The fact that these clones were resistant to up to 12 antibiotics suggests that these clones may also have a better ability to either gain or retain antibiotic-resistant genes during the STP process.;